Cyclic Voltammetry Method for Analysis of Phosphate Concentration in Water - Agustin, Qomariyah; Setiarso, Pirim (Jurnal Pijar Mipa, 2024)
Phosphate is a nontoxic element but a limiting element for productivity. Several methods have been established to analyze the phosphate concentration in water. This study aims to analyze phosphate concentration in water using the voltammetry method using cyclic voltammetry. Cyclic voltammetry is an electroanalytical method that measures the current outcome of oxidation-reduction reactions in response to the potential. The current outcome is directly proportional to the phosphate concentration in the solution. The calibration curve was formed from the KH2PO4 standard solution using concentrations of 0.1 mg/L, 0.2 mg/L, 0.4 mg/L, 0.8 mg/L, and 1.6 mg/L. The voltammogram showed that the analyte does not have an anode peak current (Ipa), which means that the analyte solution did not have an oxidation reaction, so the cathode peak current (Ipc) value was used. Based on the calibration curve, the linear regression graph with a straight-line equation is y = -0,00000645632x - 0,000208737 with R2 of 0,99737. Meanwhile, this cyclic voltammetry method was validated by calculating the LOD and LOQ values; the results are 0.1034 mg/L and 0.3134 mg/L, respectively. Hence, based on the analysis of phosphate concentration in water samples, this method works satisfactorily and is suitable for routine analysis because of its advantages.